دراسة تراكم بعض العناصر الثقيلة عند نوعي الطحالب (rubens Jania ,Galaxaura lapidescens) في شاطئ اللاذقية - النسر, امينة; عبد الله, سوزان (Latakia University Journal -Biological Sciences Series, 2018)
Heavy metals in water are accumulated in living organisms through the food chain, starting from algae and ending by fish, which is considered as main food for humans. Therefore, this study aimed to estimate the concentration of heavy metals (Zn, Cu, Pb and Cd) in the water of two locations (Ras Alshamra and Ras Ibn Hani) on the shore of Lattakia City and in two algae species (jania rubens and Galaxaura lapidescens). The results showed a significant difference in the concentration of heavy metals in the water of the two locations, where Ras Ibn Hani had higher concentrations than Ras Alshamra. This differences in concentrations are due to the presence of various human activities and to a higher number of fishing boats in Ras Ibn Hani comparing to Ras Alshamra. The analysis of algae species showed a higher level of heavy metals in Galaxaura lapidescens than the level in jania rubens. The comparison of heavy metal concentrations between water and algae showed similar patterns. Zn was present in the highest concentration while Cd was in the lowest one. The concentration of heavy metals showed the following order: Zn> Pb> Cu> Cd. يتم تراكم العناصر الثقيلة الموجودة في المياه في الكائنات الحية عبر السلسلة الغذائية، بدءاً من الطحالب وانتهاءاً بالأسماك التي تعد مصدراً أساسياً لغذاء الإنسان. هدف هذا البحث تقدير تراكيز العناصر الثقيلة (الزنك و النحاس والرصاص والكادميوم) في مياه موقعين على شاطئ مدينة اللاذقية (رأس الشمرة و رأس ابن هاني)، وعند نوعين من الطحالب (rubens Jania and Galaxaura lapidescens) . أظهرت النتائج تبايناً واضحاً في تركيز العناصر الثقيلة بين مياه الموقعين المدروسين، حيث كان تركيز كافة العناصر المدروسة أكثر ارتفاعاً في موقع رأس ابن هاني مقارنة بموقع رأس الشمرة، ويعود ذلك لتعرض موقع رأس ابن هاني لنشاطات بشرية متنوعة ولوجود وعمل مراكب الصيد بكثافة أكبر مما هو عليه الحال برأس الشمرة. تباين نوعي الطحالب باحتوائهما على العناصر الثقيلة، حيث وجد ارتفاعاً بكمية العناصر الثقيلة عند النوع Galaxaura lapidescens مقارنة بالنوع rubens Jania . عند مقارنة تراكيز العناصر الثقيلة في المياه مع مثيله عند الطحالب تبين وجود تشابهاً بترتيب محتواهما من العناصر، حيث احتل الزنك اعلى نسبة في حين تواجد الكادميوم بأقل نسبة، وكان ترتيب تركيز العناصر الثقيلة هو: الزنك > الرصاص > النحاس > الكادميوم.